The associations of continuity of care with inpatient, outpatient, and total medical care costs among older adults with urinary incontinence - Eunkyung Han; Wankyo Chung; Antonio Trujillo; Joel Gittelsohn; Leiyu Shi (BMC, 2023)
Abstract Introduction Urinary incontinence is a significant health problem with considerable social and economic consequences among older adults. The objective of this study was to investigate the financial impact of continuity of care (CoC) among older urinary incontinence patients in South Korea. Methods We used the NHIS-Senior cohort patient data between January 1, 2010, and December 31, 2010. Patients who were diagnosed with urinary incontinence in 2010 were included. Operational definition of CoC included referrals, number of providers, and number of visits. A generalized linear model (GLM) with γ-distributed errors and the log link function was used to examine the relationship between health cost and explanatory variables. Additionally, we conducted a two-part model analysis for inpatient cost. Marginal effect was calculated. Results Higher CoC was associated with a decrease in total medical cost (-0.63, P < .0001) and in outpatient costs (-0.28, P < .001). Higher Charlson Comorbidity Index (CCI) score was a significant predictor for increasing total medical cost (0.59, P < .0001) and outpatient cost (0.22, P < .0001). Higher CoC predict a reduced medical cost of $360.93 for inpatient cost (P = 0.044) and $23.91 for outpatient cost (P = 0.008) per patient. Conclusion Higher CoC was associated with decrease in total medical costs among older UI patients. Policy initiatives to promote CoC of older UI patients in the community setting could lead to greater financial sustainability of public health insurance in South Korea.